PENGEMBANGAN BUKU AJAR PENATAAN SANGGUL SIMPOLONG TETTONG PADA MATA KULIAH PENATAAN SANGGUL MENINGKATKAN HASIL BELAJAR MAHASISWA JURUSAN PKK KONSENTRASI TATA RIAS FAKULTAS TEKNIK UNM - Burhanuddin, Izmi; Syamsidah, Syamsidah; Nur Maida, A (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Science and technology are very helpful in order to accelerate human work, for this reason human resources are needed that have high productivity and work efficacy so that they are able to produce the latest innovations that can meet market share needs. Education is one attempt that made to form human resources so that they can become someone who is able to analyze and be able to create the latest innovations. Many educational practitioners believe that the use of media or tools really helps the learning process activities both inside and outside, especially helping to improve student learning outcomes. In the Family Welfare Education Undergraduate Program with a concentration in Cosmetology, Makassar State University, there is a bun styling course, one of the subjects of which is Simpolong Tettong bun. The learning method currently established is a conventional learning system with the lecturer as the main source who demonstrates how to make Simpolong Tettong bun. This textbook on the Simpolong Tettong bun material was created by the author himself and is expected to add to the repertoire and references of learning media for bun styling courses. Why a textbook? Because it contains tutorials with practical explanations, easy to brought along and re-read anytime and anywhere. Research and Development (R&D) is a type of research which is used for produce certain products, and examine the efficacy of these products. The development model used by researchers is the Thiangarajan model (1974) using the 4-D model, by the definition of Define, Design, Development and Dissemination, because it is more appropriate to use as a principle to develop teaching materials that aim to improve student learning outcomes in PKK Department of Cosmetology Concentration at FT UNM.